The performance of concrete filled steel tube columns under post-earthquake fires. (November 2018) - Talebi, Elnaz; Korzen, Manfred; Hothan, Sascha
Abstract: In this study, a nonlinear three-dimensional finite element (FE) model was developed and validated to investigate the response of concrete filled tube (CFT) columns subjected to post-earthquake fires. Three steps were considered successively in the modelling, namely, cyclic, thermal and structural analyses. Outputs from the cyclic loading including residual deformations were imposed as an initial condition to the thermal-stress model, imitating the seismic response of the column. Subsequently, a nonlinear sequentially thermal-stress analysis was conducted to simulate the fire response of column after the earthquake. The proposed FE model was validated by comparing the simulation results with the observations of full-scale fire and cyclic tests available in the literature. The validated numerical model was then used to study the behavior of CFT columns under the combined action of earthquake and fire as a multi-hazard event. Three probable seismic damage scenarios were considered in the column, namely, middle length, bottom and top end region damages. The level of damage was assumed as a high damage level, presuming that the column reached 50% of its lateral resistance while still maintaining its overall stability after the earthquake. The results showed that the top and bottom end region damages have not significantly influence the fire response of the damaged column. Besides, the column with the middle span damage performed a lesser fire resistance time owing to the coincidence of damage location to that of onset of global buckling. Highlights: We studied the concrete filled steel tube (CFT) column fire response after the earthquake. CFT column with the damage at the top and bottom behaved similar to the intact one at fire. CFT column with the seismic damage at the middle length resisted fire less than other cases. In general the seismically damaged CFT columns failed in global buckling mode at fire.